Distinct sulfur saturation histories within the Palaeogene Magilligan Sill, Northern Ireland: implications for Ni – Cu – platinum group element mineralisation in the North Atlantic Igneous Province - Lindsay, Jordan James; Hughes, Hannah S. R.; Smyth, Dermot; McDonald, Iain; Boyce, Adrian J.; Andersen, Jens C. Ø. (NRC Research Press (a division of Canadian Science Publishing), 2019)
The ∼60 m thick Magilligan Sill is part of the British Palaeogene Igneous Province in the North Atlantic. The sill comprises layers of dolerite and olivine gabbro, and it intrudes a thick sequence of Mesozoic mudstones and marls, which are locally baked at the sill margins. Since 2014, the sill has been an exploration target for orthomagmatic Ni – Cu – platinum group element (PGE) sulfide mineralisation analogous to the Noril’sk-Talnakh intrusion in Russia. We present new petrological, geochemical, and S isotope data to assess the prospectivity of the sill and the underlying magmatic plumbing system. Most sulfides in the dolerite portions of the sill are <50 μm in size and comprise only pyrite with PGE abundances below the detection limit. In the olivine gabbros, >150 μm size pentlandite, chalcopyrite, and pyrrhotite grains contain <4 ppm total PGE, 1460 ppm Co, and 88 ppm Ag. Pyrite from the dolerites have δ34S ranging from −10.0‰ to +3.4‰ and olivine gabbro sulfides range from −2.5‰ to −1.1‰, suggesting widespread crustal contamination. The S/Se ratios of sulfides in the dolerites and olivine gabbros range from 3500 to 19 500 and from 1970 to 3710, respectively, indicating that the latter may have come from upstream in the magma plumbing system. The Magilligan Sill records multiple injections of mafic magma into an inflating sill package, each with distinct mechanisms towards S saturation. Whilst the sulfide minerals in the sill do not constitute significant mineralisation themselves, detailed in situ studies highlight a divergence in S saturation histories and suggest that a larger volume of olivine gabbro sulfides at depth may be prospective. The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.